Determination of Natamycin in Turkish Yoghurt - Dilek Bilgic Alkaya; Ozlem Karalomlu (International Journal of Analytical Chemistry)
This study was aimed at developing RP-HPLC method for determination of natamycin in Turkish yoghurt. Chromatographic separation was achieved on a C8 column (150 mm × 4.6 mm × 5 µm) with a mobile phase of methanol : water : acetic acid (12 : 8 : 1 v/v/v), at 1 mL/min flow rate with a detection of 303 nm. Natamycin was spiked into handmade yoghurt samples and used for validation. The method has been fully validated according to ISO 9233-2, 2007 (IDF 140-2, 2007). It was successfully applied to determination of 28 different Turkish yoghurt products. Findings dealing with the presence of natamycin in cheese samples are presented.